Photogrammetric techniques for 3D underwater record of the Late-Imperial Torre Santa Sabina’s shipwreck - Auriemma, Rita; Calantropio, Alessio; Chiabrando, Filiberto; Coluccia, Luigi (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The possibility offered nowadays by the adoption of digital photogrammetry techniques allows one to virtually reconstruct the surveyed underwater assets to make them accessible also remotely, via visualization and dissemination platforms (online or offline). To improve the study of the documented cultural heritage artefacts and sites, it is crucial to adopt the right photogrammetric principles to achieve 3D metric products that are consistent and coherent with the real object of the survey. This paper is related to the photogrammetric survey of the late imperial era Roman shipwreck, located in ‘Baia dei Camerini’, Torre Santa Sabina (BR), Italy, in the framework of the project UnderwaterMuse (Italia-Croatia 2014‒2020 Interreg Cooperation Programme).